(untitled) (Journal of Informatics Education and Research, 2025)
Sustainable development strategies for agricultural livelihoods, insufficient infrastructure, and gendered socio-economic hurdles priorities rural development and women’s empowerment. This paper analyses women empowerment determinants in Jammu & Kashmir using primary survey data (N = 471). It identifies leverage points where generative AI, such as large language models like ChatGPT, could create scalable, context-sensitive interventions. The study validates the survey instrument (Cronbach’s α = 0.918) and assesses the impact of education and employment on empowerment using correlation, regression (R² = 0.661), and ANOVA analyses. Education variables, such as personal growth, economic independence, and awareness of rights, strongly predict empowerment. However, some attitudinal items, such as leadership aspiration, have complex or negative coefficients, highlighting institutional and socio-cultural frictions. Based on these findings, the paper proposes using generative AI to (a) increase access to localised educational content and skills training, (b) aid evidence-based policy design through automated literature synthesis and data interpretation, (c) provide livelihood and market-information services for rural producers, and (d) reduce gender biases through inclusive pedagogy and governance tools. Ethics (data privacy, algorithmic fairness), rural AI-readiness limits, and a phased deployment strategy are all discussed. According to the study, generative AI combined with participatory governance and domain-specific safeguards can accelerate rural development and empower women, but only if capacity building, accountability mechanisms, and localised data governance are also implemented.